2000
DOI: 10.1111/j.1741-3737.2000.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard Work Schedules and Marital Instability

Abstract: ࡗ Nonstandard Work Schedules and Marital InstabilityBased on subsample of 3,476 married couples drawn from two waves of the National Survey of Families and Household, this study examines the extent to which working evening, night, or rotating schedules and weekends affects the likelihood of marriages ending in separation or divorce within approximately 5 years. Logistic regression analysis revealed that this relationship depends on the presence of children and is specific to the type of nonstandard schedule, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
229
2
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(245 citation statements)
references
References 23 publications
8
229
2
6
Order By: Relevance
“…For women married more than 5 years, working nights increased the likelihood by three times. No effects of non-standard work schedules on marital stability were found for couples without children (Presser, 2000).…”
Section: Consequences For Partners' Psychological Well-being and Marimentioning
confidence: 90%
“…For women married more than 5 years, working nights increased the likelihood by three times. No effects of non-standard work schedules on marital stability were found for couples without children (Presser, 2000).…”
Section: Consequences For Partners' Psychological Well-being and Marimentioning
confidence: 90%
“…For example, a welldesigned cohort study that followed more than 13,000 men and women found that separation or divorce rates among night workers were six times higher than those of day workers 31) . The present study demonstrated that poor quality of life is linked to poor mental health.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effect of shift status at the individual level, women were categorized into two groups: women who worked day shifts and women who worked evening/ night/rotating shifts. Shift status was also assessed at the couple level; women were categorized into two groups: women who worked the same shift as their husbands and women who worked opposite shifts from their husbands (Presser, 2000).…”
Section: Anxiety (State Anxiety Scale; Spielberger 1972)mentioning
confidence: 99%